A Self-Adaptive Back-Off Algorithm Based on Collision Probability and Expiration Probability of Beacons in VANET - Weiwan Liu; Zhijia Chen; Nanjie Liu; Hao Zhong; Haitao Zhao (Dianxin kexue)
In order to improve the broadcast reception rate in VANET, the conclusion that the relationship between collision probability and minimum contention window size and the relationship between expiration probability and minimum window size were reached by building Markov model. According to this conclusion, a minimum contention window size adjustment back-off algorithm called CEB was proposed, it is on the basis of the relative size between the number of expiration beacons and pre-set threshold. Simulations were done to compare the performance of CEB, RBEB and BEB, and the results show that the performance of the new proposed algorithm is better than that of RBEB and BEB.